2000
DOI: 10.1097/00007890-200003270-00021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cold Ischemia Time, Pretransplant Anti-Porcine Antibodies, and Donor/Recipient Size Matching on Hyperacute Graft Rejection After Discordant Porcine to Cynomolgus Kidney Transplantation

Abstract: Organs transplanted between phylogenetically disparate species, such as from the pig into the primate, are subject to hyperacute rejection (HAR). This form of xenograft rejection is mediated by preformed natural antibodies and is believed to occur invariably in discordant xenografts thus leading to rapid destruction and complete thrombosis of the graft. Recent data, however, have shown that in the porcine to cynomolgus monkey setting, HAR is not inevitably seen after porcine kidney transplantation. The influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…As shown in this study (Fig. 1) and by others (E. Cozzi, personal communication), the analysis of the recipient's serum anti‐porcine antibodies by either hemolytic assays on porcine red blood cells [3] or by non‐specific FACS analysis of antibody binding on PBL [7], reveals significant changes in recipient antibody titer only in a subset of episodes of xenograft rejection. Therefore, measurement of plasma C3a or sC5b‐9 levels could be used as an additional marker for early immunologically mediated damage of the xenograft.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…As shown in this study (Fig. 1) and by others (E. Cozzi, personal communication), the analysis of the recipient's serum anti‐porcine antibodies by either hemolytic assays on porcine red blood cells [3] or by non‐specific FACS analysis of antibody binding on PBL [7], reveals significant changes in recipient antibody titer only in a subset of episodes of xenograft rejection. Therefore, measurement of plasma C3a or sC5b‐9 levels could be used as an additional marker for early immunologically mediated damage of the xenograft.…”
Section: Discussionsupporting
confidence: 55%
“…The reason for the absence of alterations in systemic anti‐porcine antibody levels during the majority of episodes of AVR might be the trapping of the antibodies in the xenograft itself. This hypothesis is supported by the fact that in a non‐life‐supporting model of discordant pig‐to‐cynomolgus xenotransplantation established in our laboratory [7] as well as in a model of heterotopic cardiac transplantation without post‐operative immunosuppression [20] an increase in anti‐porcine antibody levels was in fact observed but only after surgical removal of the xenograft. As long as the graft was perfused in situ, no significant changes in antibody levels were described.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…On the other hand, the ability to estimate and select an organ which is proper in size and weight before transplant may have advantages, such as enhancement of survival and function of the xenograft, 31 as well as a lower incidence of hyperacute rejection. 32 In this study, the mean of total liver weight was 696.6 ± 91.3 g. The percentage of whole liver weight to body weight was approximately 2.5% in pigs and 2% to 4% in humans. Hence, our data suggested that the relation of the human liver/body weight is similar to the pig liver/body weight.…”
Section: Discussionmentioning
confidence: 49%